Educational Incompatibility: The Necessary Interdisciplinarity of Overeducation - Gomes Duarte Gomide dos Santos, Igor (Riviera Publishing, 2022)
Introduction: the fragility of academic discussions about overeducation is often limited to the scope and macroeconomic consequences of these discussions, ignoring the social, anthropological, political, and educational aspects of education. This study aims to find out and analyze how important education must take precedence. Method: This study uses a qualitative descriptive method with the type of library research (Library Research). Publications were searched in four scientific databases: Scielo, Thesis and Dissertation Digital Library (BTD), Portugal Scientific Open Access Repository (RCAAP), and DIALnet. Results: The development of academic research on educational dissonance recapitulated, placed its findings within the scope of economics, and demonstrated that, to date, economics has remained the main driving force of study in the field. Interdisciplinary tools are essential for dealing with the integrality of the problem of over-education in order to propose viable solutions. Conclusion: Now, if the solutions found so far in economics are not feasible (given the obvious contradictions of reality), it is necessary to overcome educational incompatibility from an interdisciplinary prism, which results in points such as the formulation and evaluation of public policies.